The Right of Internally Displaced Persons to Local Government: Ukraine's Experience and International Practice - Білоус-Осінь, Тетяна Ігорівна; Білоус-Осінь, Т. І.; Билоус-Осень, Татьяна Игоревна; Bilous-Osin, Tetiana I.; Стрельников, Андрій Вікторович; Стрельников, А. В.; Стрельников, Андрей Викторович; Strelnykov, Andrii V.; Strelnykov, Andriy; Корнута, Людмила Михайлівна; Корнута, Л. М.; Корнута, Людмила Михайловна; et al. (Geplat, 2020)
The right for local government is the pledge for the state democratic system. The qualified bond between public management and values, which a member of the community gets, is formed by means of people’s participation in local issues’ government. That is why the opportunity absence to participate in local government for any member provokes negative consequences and mediates the change from the citizen status into a hybrid-civilian one. The research is focused on the law security legal regulation on the local government of Ukraine and on the detection of weak spots in relation to the inner displaced people. The authors examine international legal standards of law implementation on the local government. Based on this, there were offered the amendments to the current legislative control of law implementation of the inner displaced people on the local government.

Право на місцеве самоврядування є запорукою державного демократичного устрою. Кваліфікований зв’язок між державним управлінням та цінностями, який отримує член громади, формується за допомогою участі людей в управлінні місцевими справами. Ось чому відсутність можливості брати участь у місцевому самоврядуванні будь-якого члена провокує негативні наслідки та опосередковує зміну статусу громадянина на гібридно-цивільний. Дослідження зосереджене на правовому забезпеченні правового регулювання місцевого самоврядування в Україні та на виявленні слабких місць щодо внутрішньо переміщених осіб. Автори досліджують міжнародно-правові стандарти реалізації законодавства про місцеве самоврядування. Виходячи з цього, були запропоновані зміни до чинного законодавчого контролю за виконанням законодавства внутрішньо переміщеними особами на рівні місцевого самоврядування.

Право местного самоуправления - залог демократического строя государства. Квалифицированная связь между государственным управлением и ценностями, которую получает член сообщества, формируется посредством участия людей в управлении местными делами. Поэтому отсутствие у любого члена возможности участвовать в местном самоуправлении влечет за собой негативные последствия и опосредует переход от статуса гражданина к гибридно-гражданскому. Исследование сфокусировано на правовом регулировании правовой безопасности местного самоуправления в Украине и на выявлении слабых мест по отношению к внутренним перемещенным лицам. Авторы исследуют международно-правовые стандарты применения законодательства о местном самоуправлении. Исходя из этого, были предложены поправки к действующему законодательному регулированию исполнения закона внутренне перемещенными лицами на уровне местного самоуправления.
Bilous-Osin Т. The Right of Internally Displaced Persons to Local Government: Ukraine's Experience and International Practice / T. Bilous-Osin, A. Strelnykov, L. Kornuta, O. Lavrenova // The Revista Estudos Estudos & Práticas. – № 4. – Geplat, 2020. – 16 р.
Keywords: law; local government; forced displaced persons; Ukraine; закон; місцеве самоврядування; вимушені переселенці; Україна; право; местное самоуправление; вынужденные переселенцы; Украина; Research Subject Categories::LAW/JURISPRUDENCE